Portfolio Management in Times of Elevated Risk. Safe-Haven and Hedge Assets in CAPM Setting - Ewa Feder-Sempach (Finanse i Prawo Finansowe)
The purpose of the article. The purpose of the article is to present the safe-haven concept according to the latest academic literature and distinguish it from the hedge and diversifier terms that are sometimes used interchangeably by researchers and portfolio managers. The ultimate goal of the paper is to place the safe-haven and hedge assets in the portfolio theory setting by introducing the negative beta parameter as stated in the Capital Asset Pricing Model. According to the literature, this article proposes a few approaches to identify and characterize safe-haven assets and to discover the perspective and outline further research in the portfolio theory.